Developing The Welfare of The Fatayat Group of Mangunsari Village Gunungpati Semarang Through Socioecopreneurship: Pengembangan Kesejahteraan Kelompok Fatayat Desa Mangunsari Gunungpati Semarang melalui Socioecopreneurship - Devy Rinjani, Ersila; Jauharin Farda, Ummu; Himawati, Ulya; Lia Sari, Risti; Indiyarti Putri, Linda (Universitas Lancang Kuning, 2024)
The urgency of this service is based on women in lower middleclass communities, especially in the Fatayat Ds. Salakan who always tries to escape the shackles of economic difficulties. The emergence of Socioeconomics which is widespread and developing in society is a signal that productivity and creativity are the main elements in improving the welfare of life. The Socioeconomic-based mentoring concept implemented is not only focused on activities to improve the economic level of the assisted residents, but also pays attention to environmental and social issues. This service aims to develop productivity and creativity using a socioecopreneurship approach with the focus of service being on three things, including (1) Providing counseling and outreach to assisted subjects with the theme: